PERCOBAAN PENDAHULUAN MENGGERGAJI BATANG KELAPA - Osly Rachman; S Karnasudirdja (Pusat Penelitian dan Pengembangan Hasil Hutan, 1984)
Fourteen air dry logs of coconut trunk were sawn into boards and squares of varying dimensions following a